ANALISIS PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DALAM MEMILIH REAL PROPERTY MELALUI DIGITAL MARKETING SEBAGAI VARIABEL INTERVENING DI YOGYAKARTA - Rufaida Setyawati; Suhartono Suhartono; Pungki Nindia Asmoro (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
The research aims: 1) to determine the effect of product quality, price and digital marketing on purchasing decisions of real estate consumers in Yogyakarta. 2) To find out the effect of product quality and price on digital marketing for real estate consumers in Yogyakarta. 3) To find out the effect of product quality and price on purchasing decisions through digital marketing for real estate consumers in Yogyakarta. The variables of this study are product quality, price, digital marketing and purchase decisions. The population in this study were all consumers of Real Property in Yogyakarta. The sampling technique used in this study was purposive sampling. Purposive sampling technique is a technique of determining the sample with certain considerations. The method of collecting data using a questionnaire. The analysis technique used is multiple linear regression with a significance level of 5%. The results showed that product quality has no direct effect on digital marketing. Price has a direct effect on digital marketing. Product quality has a direct effect on purchasing decisions. Price has a direct effect on purchasing decisions. This means that the price is a factor in purchasing decisions for real property consumers in Yogyakarta. Digital marketing has a direct effect on purchasing decisions. Product quality directly affects purchasing decisions through digital marketing. This means that digital marketing can be intervened in the influence of product quality on consumer purchasing decisions for real property in Yogyakarta. Price has a direct effect on purchasing decisions through digital marketing.